2006
DOI: 10.1002/jgm.883
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear‐targeted minicircle to enhance gene transfer with non‐viral vectors in vitro and in vivo

Abstract: Our results indicate that the combination of a minicircle DNA construct with a TetR nuclear-targeting system is able to potentiate gene expression of non-viral vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…[33] One type of cationic lipid that is often used in DNA transfection is DOTAP. [34][35][36] Using this molecule, we have elaborated a clever strategy for the production of cationic MLs, which was outlined in a previous paper.…”
Section: Discussionmentioning
confidence: 99%
“…[33] One type of cationic lipid that is often used in DNA transfection is DOTAP. [34][35][36] Using this molecule, we have elaborated a clever strategy for the production of cationic MLs, which was outlined in a previous paper.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study analyzed the ability of a tetracycline repressor protein TetR fused to the TAT peptide to enhance nuclear import and gene expression of minicircle DNA in vivo. It was found that there was more than a 6-fold increase in gene expression in mouse lung [Vaysse et al 2006]. Another HIV protein, the integrase IN, has shown nuclear accumulation and DNA binding activity in vitro, and may be a candidate for enhancement of nonviral gene delivery [Hearps & Jans 2006].…”
Section: Nls:dna Conjugatesmentioning
confidence: 99%
“…When EBV nuclear antigen (EBNA)-1 expressing cells were cytoplasmically microinjected with plasmids containing the oriP DTS, increased gene expression was detected when compared to plasmids lacking oriP [Langle-Rouault et al 1998]. More recently, combinations of the tet operator and a modified tetracycline repressor containing an NLS (tetO and TetR-NLS, respectively) have been used in cis and trans to show that nuclear import can be controlled and enhanced by protein-DNA interactions [Vaysse et al 2004;Vaysse et al 2006]. When multiple copies of the tetO sequence were cloned into a plasmid and transfected into cells expressing TetR-NLS, gene expression increased almost 20-fold in growth-arrested cells, and nuclear localization increased by 4-fold.…”
Section: Sequence-specific Nuclear Import Of Plasmid Dnamentioning
confidence: 99%
“…To address this problem, one important issue is how to overcome the inefficient translocation of plasmid entities to cell nucleus. It is possible to attach the plasmid cargos with a nuclear localization signal peptide to conquer the barrier (Vaysse et al, 2006). Finally, the presence of bacterial DNAs naturally rich in CpG dinucleotides on plasmids is known to cause transcriptional silencing of the transgene in cells.…”
Section: Discussionmentioning
confidence: 99%